Peningkatan pengetahuan dan ketrampilan bagi pemuda GMIST Jemaat Kuma tentang budidaya lele di sistem akuaponik: Enhancing Knowledge and Skills of GMIST Kuma Youth on Catfish Farming in an Aquaponics System - Mose, Iske; Ulaan, Magdalin (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  Church youth hold strategic potential in fostering community-based economic independence, particularly in island regions with limited access to technology and entrepreneurial training. This community service program aimed to enhance the knowledge and skills of GMIST Jemaat Kuma youth in catfish farming using an aquaponics system. Aquaponics integrates fish farming and plant cultivation into a closed-loop ecosystem that is land-efficient, sustainable, and environmentally friendly. The activity employed a combination of theoretical training, practical installation workshops, and field mentoring. The program was conducted in Tabukan Tengah District, Sangihe Islands Regency, and involved youth participants from Kuma and Kuma I villages. Results showed increased participants’ understanding of aquaponics concepts, improved skills in assembling simple systems, and strong enthusiasm for adopting the technology sustainably. A stimulus package in the form of one complete aquaponics unit supported continued application and served as an ongoing learning resource. This initiative demonstrates a tangible contribution to local capacity building, household food security, and youth empowerment through resource-based social entrepreneurship.  Keywords: Church youth, Aquaponics, Catfish, Empowerment, Fish farming   ABSTRAK  Pemuda gereja memiliki potensi strategis dalam membangun kemandirian ekonomi berbasis komunitas, terutama di daerah kepulauan yang memiliki keterbatasan akses terhadap teknologi dan pelatihan wirausaha. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan pemuda GMIST Jemaat Kuma dalam budidaya ikan lele menggunakan sistem akuaponik. Sistem ini mengintegrasikan budidaya ikan dan tanaman secara simultan dalam satu ekosistem tertutup yang efisien, hemat lahan, dan ramah lingkungan. Metode pelaksanaan meliputi pelatihan teori, praktik pemasangan instalasi akuaponik, serta pendampingan teknis di lapangan. Kegiatan dilaksanakan di Kecamatan Tabukan Tengah, Kabupaten Kepulauan Sangihe, dan melibatkan pemuda dari Kampung Kuma dan Kuma I. Hasil kegiatan menunjukkan peningkatan pemahaman peserta terhadap konsep akuaponik, kemampuan merakit sistem sederhana, serta antusiasme tinggi dalam menerapkan teknologi tersebut secara berkelanjutan. Stimulus bantuan berupa satu set sistem akuaponik mendukung keberlanjutan praktik dan menjadi sarana edukasi lanjutan. Kegiatan ini memberikan kontribusi nyata terhadap peningkatan kapasitas lokal, ketahanan pangan keluarga, serta pemberdayaan pemuda gereja dalam kewirausahaan berbasis sumber daya lokal. Kata kunci: Pemuda gereja, Akuaponik, Lele, Pemberdayaan, Budidaya ikan